B243 Regional anesthesia role during limitation of life sustaining measures – a case report. (11th August 2022) - Correia, A; Lusquinhos, J; Santos, F
Abstract : Background and Aims: Ethical dilemmas regarding the limits of perioperative medical interventions are growing concern in clinical practice. Increasing age and associated comorbidities along with anesthetic-surgical advances presents challenges when considering questions as "whether to operate or not?" or "how to impact minimally in fragile homeostasis?". Methods: Our case report describes an 86-years-old man (Clinical Frailty Scale score 5) proposed to an emergent drainage of an intramuscular gastrocnemius abscess. Beyond their significant comorbidities (peripheral artery disease, ischemic cardiomyopathy) he was in septic shock with multiple-organ dysfunction (serum lactate 8.8 mmol/L). Intensive Care Unit (ICU) based-resuscitation team approached the patient in the ward and established a limitation of life-sustaining measures with refusal to be admitted in the ICU. However, in an expanded multidisciplinary team-meeting with Anesthesiology and Orthopedics, it was decided to operate under regional anesthesia (RA): sciatic nerve block with a popliteal approach. Results: The anesthetic cover of the surgical field allowed the source control. Thereafter, it was decided to implement fluid resuscitation and a vasopressor (noradrenaline 0.5 mcg/kg/min). The patient exhibited a favorable clinical-laboratory response leading to a reassessment of the ICU admission decision. He was admitted to an ICU-bed during 48h and transferred to a general surgical ward. After 52 days he was discharged. Conclusions: This clinical case highlights the role of RA in situations where invasiveness or aggressiveness of some intervention could overcome the acceptable risk for the patient. The RA allowed the surgical intervention with foci control whilst the additional interference with cardiovascular and respiratory systems was prevented.